2022
DOI: 10.1186/s13012-022-01217-4
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a type III hybrid effectiveness-implementation trial to evaluate scaling interoperable clinical decision support for patient-centered chronic pain management in primary care

Abstract: Background The US continues to face public health crises related to both chronic pain and opioid overdoses. Thirty percent of Americans suffer from chronic noncancer pain at an estimated yearly cost of over $600 billion. Most patients with chronic pain turn to primary care clinicians who must choose from myriad treatment options based on relative risks and benefits, patient history, available resources, symptoms, and goals. Recently, with attention to opioid-related risks, prescribing has decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In recent years, a growing number of mobilehealth technology in the management of chronic diseases has been observed [33,34]. These applications are mainly aimed at patients as end-users and primarily achieve pure data collection [35]. The integration of data accumulated through these apps in clinical nephrology practices is limited by: 1.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing number of mobilehealth technology in the management of chronic diseases has been observed [33,34]. These applications are mainly aimed at patients as end-users and primarily achieve pure data collection [35]. The integration of data accumulated through these apps in clinical nephrology practices is limited by: 1.…”
Section: Discussionmentioning
confidence: 99%
“… A Type 2 hybrid trial has a dual focus on intervention effectiveness and implementation outcomes (e.g., Gilmartin et al's 14 evaluation of the effectiveness of the rural transitions nurse program; Hassett et al's 15 implementation of patient‐reported outcomes for symptom management in oncology practice). A Type 3 hybrid trial focuses primarily on implementation outcomes while also exploring effectiveness outcomes as they relate to uptake, integration, and fidelity of the intervention in real‐world settings (e.g., Bonafide et al's 16 evaluation of a safety huddle‐based intervention; Salloum et al's 17 evaluation of clinical decision support for patient‐centered chronic pain management). …”
Section: Types Of Hybrid Trialsmentioning
confidence: 99%
“…A Type 3 hybrid trial focuses primarily on implementation outcomes while also exploring effectiveness outcomes as they relate to uptake, integration, and fidelity of the intervention in real‐world settings (e.g., Bonafide et al's 16 evaluation of a safety huddle‐based intervention; Salloum et al's 17 evaluation of clinical decision support for patient‐centered chronic pain management).…”
Section: Types Of Hybrid Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, CDS focused on chronic pain could support PCPs in providing safer and more patient-centered care for patients. 11 While quantitative evaluations of existing chronic pain CDS tools exist, 12–14 current work does not assess PCPs’ experience and behavior with adopting and using chronic pain CDS tools. Qualitative evaluations support the thorough examination of factors associated with CDS uptake and use, as most CDS tools target user behavior.…”
Section: Introductionmentioning
confidence: 99%